The Influence of Word of Mouth on The Decision to Purchase Handphone Case at Devi Phone Store - Yomeini Margareth S (Jurnal Mantik, 2021)
This study aims to determine how the influence of word of mouth on purchasing decisions. The population in this study are consumers of Devi Mobile per month, amounting to 180 people. Samples were taken as many as 65 respondents using the Slovin formula. Regression analysis method used is simple linear regression and to test the hypothesis used t test and f test at a significant level or alpha = 5%. The research data were analyzed or processed using the SPSS version 25 program. Based on the research results, it was 0.382 or 38.2%. This shows that the word of mouth variable (X) can explain the purchasing decision variable (Y) by 38.2%, the remaining 61.8% (100% - 38.2%) is explained by other variables outside this research model. In the simple linear regression test results obtained the following regression equation: Y = 8.978 + 0.869X + e. The results of the hypothesis test state that: H1 is accepted, it can be seen from the tcount value is 6.246 >ttable 1.997 and with a significance value of 0.000 <0.05 then word of mouth has an effect on purchasing decisions.